Gaining masculine power through guns? The impact of masculinity threat on attitudes toward guns - Kachel, Sven; Bloch, Tibor; Bosson, Jennifer K.; Lorenz, Lea L.; Steffens, Melanie C. (Frontiers in Psychology, 2024)
Gun violence is a serious problem in the U.S. and elsewhere and more so among men than women. We conducted an experiment to examine if men whose masculinity was threatened are more attracted to guns than non-threatened men, presumably to compensate for the threat. After completing a gender knowledge test, men (N = 168) randomly received either false masculinity threatening (experimental condition) or masculinity affirming (control condition) feedback. Subsequently, we measured men's attitudes towards guns and their choice of a gunrange voucher. Men whose masculinity was threatened (vs. affirmed) showed more positive attitudes towards guns and were more likely to choose the voucher. Both effects were statistically significant when the whole sample was analyzed and when very strict exclusion criteria were applied. However, when data exclusions were based on a suspicion check, effects were statistically significant only when a covariate was included (i.e., social dominance orientation, patriotism, or experience with guns). We discuss reasons for this mixed evidence, including the possibility that suspicion regarding the masculinity feedback could itself be a compensatory reaction to threat.